Investigation of effects of cation-exchanged clay fillers in PE-blended starch composite films - Teo, Yao Zhong (2016)
The aim of this work is to investigate the effects of cation-exchanged clay fillers in PE blended starch (PETPS) on its mechanical, degradation and barrier properties. 50wt% starch blended PE composite blown films are extruded with 2.5wt% cation-exchanged clay in a 2 step process. The composite films are subsequently tested for presence of accelerated degradation and improvement in barrier properties, and the results are compared with pure PE and PETPS blown film with the absence of clay fillers. As expected, the presence of clay platelets in PETPS blend resulted in good mechanical and barrier properties. Apart from this, results also indicated that Fe3+ and Ni2+ cation-exchanged clay increased rate of degradation of PETPS films. The unexchanged clay filler, however, resulted in a decreased degradation of PE rather than an increase. This suggests that any increased rate of degradation in cation-exchanged clay fillers in PETPS composite films is the result of the cation-exchanged clay. Hence, there is evidence to suggest that the addition of cation exchanged clay fillers accelerates the degradation of PETPS composite films.